A Commentary on the United Nations Convention on the Rights of the Child, 3 : the Best Interests of the Child. - Freeman, Michael (BRILL, 2007)
Constitutes a commentary on Article 3 of the United Nations Convention on the Rights of the Child. This title is part of the series, "A Commentary on the United Nations Convention on the Rights of the Child", which provides an analysis of substantive, organizational and procedural provisions of the CRC and its two Optional Protocols.